Joyce's Gnomic Epiphanies: Narrative strategies in Dubliners - Gjurgjan, Ljiljana Ina (Array, 2010)
The paper claimes that whereas Joyce's later narratives are characterised by semantic disseminations and hypermnesia (Derrida), in his early works semantic indeterminacy is created by procedures that can be described as negative epiphanies or gnomons, their semiosis depending on that which is to be substracted from the text, rather than on what the text states. These narrative procedures are characteristic of the turn-of-the-century epistemological crisis in relation to the Cartesian notions of truth, subject and narrative closure, thus radicalising the problematics of sense making to the utmost.